Psychological Profile Inventory For Adolescents In Malaysia - See , Ching Mey (Penerbit Universiti Sains Malaysia, 2010)
The Psychological Profile Inventory for Adolescents (PPIA) is developed as a tool to identify positive and negative behaviours in adolescents, and uncover the reasons for such positive or negative behaviours. PPIA can also be used to identify adolescents atrisk from psychological disorders. PPIA is suitable for use by teachers, counselors and psychologists in schools. The resulting profile drawn can be used to understand the needs of adolescents, identify those at-risk, and plan for intervention. This paper describes the development of PPIA which took into consideration the multicultural aspects of the Malaysian population